Untersuchung der Augensicherheit durch Multi-Pulsbestrahlung für LiDAR-Anwendungen - Lipp, Scarlett (KIT Scientific Publishing, 2022)
LiDAR (Light detection and ranging) represents one of the key technologies for autonomous driving. For this reason, this work is concerned with the question of eye safety of the laser-based technology. For this purpose, investigations on laser-tissue interactions, laser-induced damage thresholds and mechanisms by multi-pulse trains were performed as well as assessments according to the laser safety standard in Europe (DIN EN 60825) and the USA (ANSI Z.136) were applied.